2003
DOI: 10.1038/sj.onc.1206043
|View full text |Cite
|
Sign up to set email alerts
|

NF-κB is constitutively activated in high-grade squamous intraepithelial lesions and squamous cell carcinomas of the human uterine cervix

Abstract: We demonstrate, for the first time, that the transcription factor NF-jB is constitutively activated during human cervical cancer progression. Immunohistochemical analysis was done using 106 paraffin-embedded cervical tissue specimens of different histological grades. In normal cervical tissue and low-grade squamous intraepithelial lesions, p50, RelA and IjB-a were mainly localized in the cytosol, whereas in high-grade lesions and squamous cell carcinomas, p50-RelA heterodimers translocated into the nucleus wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

10
108
2
2

Year Published

2005
2005
2017
2017

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 142 publications
(122 citation statements)
references
References 52 publications
10
108
2
2
Order By: Relevance
“…These findings in prostate tumorigenesis are consistent with previous observations in other cancer types, such as gastric (Sasaki et al, 2001), uterine cervix (Nair et al, 2003), colorectal (Yu et al, 2003), breast (Biswas et al, 2004), and head and neck squamous cell cancers , showing that NF-kB activation occurs mainly in established cancer tissues rather than in normal or premalignant lesions. In the present study, NF-kB staining was not significantly linked to other known prognostic factors of biochemical relapse such as preoperative PSA levels, surgical margins or Gleason grade.…”
Section: Discussionsupporting
confidence: 92%
“…These findings in prostate tumorigenesis are consistent with previous observations in other cancer types, such as gastric (Sasaki et al, 2001), uterine cervix (Nair et al, 2003), colorectal (Yu et al, 2003), breast (Biswas et al, 2004), and head and neck squamous cell cancers , showing that NF-kB activation occurs mainly in established cancer tissues rather than in normal or premalignant lesions. In the present study, NF-kB staining was not significantly linked to other known prognostic factors of biochemical relapse such as preoperative PSA levels, surgical margins or Gleason grade.…”
Section: Discussionsupporting
confidence: 92%
“…The cellular changes we observed in the cervical epithelium following 3-MC treatment closely resemble the progressive stages of human squamous cell carcinoma that constitute 80% of human cervical cancer. Nair et al (2003) have reported that there is an increased nuclear localization and DNA-binding activity of NF-kB as the grade of human cervical cancer progresses, which was also reflected in our 3-MC model, making it a suitable model for evaluating the synergistic effect of paclitaxel and curcumin in vivo. To validate the results obtained in the 3-MC model, we used the xenograft model using human cancer cell line HeLa, which has HPV oncogenes integrated within.…”
Section: Discussionmentioning
confidence: 91%
“…The nuclear expression of NF-kB might be considered as an indicator of malignant transformation and, interestingly, it is well demonstrated that NF-kB is constitutively activated during human cervical cancer progression (Nair et al, 2003). Reports also indicate that inhibition of NF-kB ameliorates the pathogenesis and overcomes therapeutic resistance (Ahn et al, 2007).…”
Section: Discussionmentioning
confidence: 99%
“…Overall survival dependent on cytoplasmic (C and E) and nuclear (D and F) RelA overexpression for the whole study cohort (C and D) as well as for the subgroup of node-negative patients (E and F). Sweeney et al, 2004), endometrial (Pallares et al, 2004), hepatocellular (Tai et al, 2000) and oral (Nakayama et al, 2001) as well as cervical (Nair et al, 2003) carcinoma. Reports on RelA expression in pancreatic cancer are sparse.…”
Section: Discussionmentioning
confidence: 99%